Decoding Zee 4.0. - Rahman Naziya Alvi (Mumbai BW Businessworld Media Pvt. Ltd., 2020)
The content major is seeking to rediscover its mojo by putting together a plan that in the main involves a rejig of its leadership team and integration of various business and content verticals with revenue maximization as its focus.